An Islamic perspective on the protection of the mind and attainment of happiness - Sulaiman, Kabuye Uthman (Journal of Education and Social Science (JESOC), 2017)
The purpose of the guidance sent by Allah through Prophets and Messengers (peace and blessings of Allah be upon them) is for human beings to achieve happiness in this world and the Hereafter. Happiness is the ultimate purpose of all human endeavours; the goal pursued by all human beings regardless of their religious and cultural differences. What is happiness? How is it achieved? Answers to these questions are crucial to the understanding of the different worldviews of life and man. The contention of this paper is the achievement of happiness in Islam through the protection of the mind, which is one of the higher objectives of Islamic Law – Maqasid al-Shari‘ah. Others are protection of religion, life, progeny and wealth. The paper: firstly, describes the importance of the mind and happiness. Secondly, explains the merits of the mind. Thirdly, explicates the interconnectedness of the mind and happiness. Fourthly, describes how Islam preserves the mind and promotes happiness, and lastly, elucidates the limitations of the mind and the need for revelation. The goal of this paper is to show that happiness is unattainable without the protection of the mind from discontentment and kufr (disbelief in Allah). In other words, the paper shows a correlation between attainment of happiness and protection of the mind. It highlights the importance of mental health. It is hoped that this work will contribute to the understanding of happiness and personal worth on the basis of the Islamic worldview